Analisis Pengelolaan Sampah Di Kapal Dan Peran Awak Kapal Terhadap Pencegahan Pencemaran Laut Dari Kapal Di Pelabuhan Tanjung Perak Surabaya - Kuncowati Kuncowati (Majalah Ilmiah Bahari Jogja, 2019)
With the increase in the number of ships in the sea transport, the impact on the marine environment is that the waste produced from ships also increases. In daily ship operations, it produces garbage such as household waste and unused dunnage consisting of plastic, paper , iron, glass, food scraps and other rubbish. If this garbage enters the sea, the sea will be polluted and the marine function will decline. In the International Convention on the prevention of pollution from the 1973/1978 MARPOL vessel on the annex V on waste (GARBAGE) regulating the disposal of garbage from ships, but still found garbage disposal by ship passengers and crew at sea with distance and provisions that are not in accordance with MARPOL 1973/1978 Annex V. Therefore, researchers analyzed the management of garbage on ships carried out by ships at the Port of Tanjung Perak Surabaya in an effort to reduce pens contamination of the sea. The research method used is the quantitative method, namely regression analysis by distributing questionnaires to 100 (one hundred) respondents of crew members who ship at the Tanjung Perak Pier in Surabaya. From the results of the regression calculation, it is obtained that the waste management factor on the ship has an effect on increasing pollution prevention from ships by 48.6% and the role factor of the crew influences the prevention of pollution from ships by 31.5%